Guidance for Processing Sushi in Retail Operations - Keith R. Schneider; Victor Garrido; W. Steve Otwell; Ray Mobley (EDIS)
This recommended guidance is for sushi and related products (raw or cooked) either in the form of individual slices or combined in rolls made with acidified rice, seafood and vegetables, or similar rolls with vegetables alone, prepared in the retail establishment by combining the necessary ingredients, and packaged for display in refrigerated cases for public sale. This document is FSHN05-09, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL 32611. Published: February 2005.